COMPORTAMENTO DOS BANCOS, POSTURAS FINANCEIRAS E OFERTA DE CRÉDITO: DE KEYNES A MINSKY - Paula, Luiz Fernando Rodrigues de (2009)
This article analyses the bank behavior and its impacts on credit supply and monetary dynamics of a capitalist economy, based on Keynes and Minsky's approaches. It is shown that although these approaches are complementary, they were elaborated in different historical contexts each associated with a specific stage of the banking system evolution. Besides, it is suggested that the contribution of these authors can provide the basis for the construction of a theory of the banking firm alternative to the neoclassical approach of banking activity. It considers the banking firm as a dynamic agent whose behavior affects both liquidity conditions, the financial framework of an economy and, consequently, the expenditures of economic agents, implying a crucial role on the determination of the level of economic activity,